2013
DOI: 10.1097/brs.0b013e31829c08c9
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmission After Spine Fusion for AdultSpinal Deformity

Abstract: Unplanned hospital readmissions after spine fusion for adult spinal deformity are common, and are most often due to surgical site infection. Patient medical comorbidities are an important part of assessing risk and can be used by providers and patients to better assess individual risk prior to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 18 publications
4
72
3
Order By: Relevance
“…Schairer reported a 90 day unplanned readmission rate of 12.3% in patients who underwent deformity surgery in his study. 11 McCormack reported 30 day unplanned readmission rates of 4.3% for anterior cervical spine fusion patients and 5.9% for posterior cervical fusion patients from 2007 through 2009. 7 His study is of particular interest because it took place at the same institution as ours, yet it reported higher readmission rates than we observed from 2011 through 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Schairer reported a 90 day unplanned readmission rate of 12.3% in patients who underwent deformity surgery in his study. 11 McCormack reported 30 day unplanned readmission rates of 4.3% for anterior cervical spine fusion patients and 5.9% for posterior cervical fusion patients from 2007 through 2009. 7 His study is of particular interest because it took place at the same institution as ours, yet it reported higher readmission rates than we observed from 2011 through 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The major complications we noted in our study were dural tears, intra-operative haemorrhage, wound sepsis and pseudarthrosis leading to instrumentation failure. Schairer et al 10 reported risk factors leading to complications requiring readmission were longer fusion length, higher patient severity of illness and specific medical comorbidities. Surgical site infection accounted for 45.6% of their 8.4% rate of readmission.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The decision to abort conservative management for surgical intervention can be difficult. Recent evidence has shown that surgically treated patients do better than conservatively managed ones in terms of pain and healthrelated quality of life (HRQOL) outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These factors could contribute to different 30-day readmission rates based on subspecialty. Previous studies have shown a range of 30-day readmission rate from 3% for joint arthroplasty to 14% for spinal deformity surgery [26,28]. If there are differences across orthopaedic subspecialties in readmission rates, then CMS-driven disincentives may be applied unequally across subspecialties.…”
Section: Introductionmentioning
confidence: 99%
“…This could result in hospitals deemphasizing those service lines and, to the degree that some of these services (such as complex spine care or Level I trauma) are available mainly at tertiary care hospitals, those disincentives could result in limiting access to care to the neediest patients. Previous studies have identified risk factors for readmission in single institutions [9,26,28]. It has been demonstrated that risk factors for readmission vary according to patient population [2]; therefore, we aim to characterize the readmission risk factors in our large, academic, tertiary care hospital to add to the body of published data.…”
Section: Introductionmentioning
confidence: 99%